Peningkatan Hasil Belajar Siswa dalam Mata Pelajaran Biologi melalui Penerapan Model Gagnon and Collay Kelas Xi MIPA2SMAN 6 Kerinci - Susanti, Nelly (Universitas Batanghari Jambi, 2022)
Application of Learning Model Gagnon and Colay in eye lesson Biologyon student class XI MIPA 2 SMA Negeri 6 Kerinci , where is the Gagnon and Collay Modelthisis a structured learning model based on theory constructivist who emphasizes on liveliness students , independence as well as development study team by intensive . Study this is study action class (Classroom Action Research), which consists of from four component in every cycle that is planning (planning), action (action), observation (observation), and reflection (refleck), done for know is with Application of Learning Model Gagnon and Collay results study student class XI MIPA2 Public High Schools 6 Kerinci could increase. Subject in study this is student class XI MIPA2 Public High Schools 6 yang totaling 20 people. In collecting the data, this research use test on every cycle and sheet observation. As for technique data analysis that is with technique descriptive data analysis qualitative and descriptive quantitative. Descriptive qualitative used in analyze result data observation or observation, while descriptive quantitative used for give description or take conclusion based on results test learning done on every cycle.Results analysis test results study student on every cycle show that level ability student class XI MIPA2 Public High Schools 6 Kerinci experience increas, thing this seen after Application of Learning Model Gagnon and Collay, lookon cycle I average value student as big as 60 and on cycle II an average of 84. This thing show that results study biology increase after Application of Learning Model Gagnon and Collay.